The Effect of Health Promotion Programs on Maternal Health Outcomes - Nayla Safira; Yusriani Yusriani (Generasi Sains Indonesia, 2025)
Maternal health remains a major public health concern in Indonesia, particularly in regions experiencing healthcare access disparities and limited maternal health literacy. This study aimed to examine the effect of health promotion programs on maternal health outcomes in Gorontalo. A quantitative quasi-experimental design with pre-test and post-test control groups was employed involving 200 women of reproductive age. The intervention consisted of structured health promotion sessions focusing on maternal nutrition, pregnancy danger signs, birth preparedness, and healthcare utilization. Data were collected through questionnaires and maternal health records and analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, and multiple regression analysis. The findings indicate significant improvements in maternal knowledge, antenatal care attendance, birth preparedness, and facility-based delivery among participants receiving the intervention. Regression results further demonstrate that health promotion was the strongest predictor of maternal health outcomes after controlling for socio-demographic factors. The findings highlight the strategic importance of integrating structured health promotion into primary healthcare systems to improve maternal health performance and reduce healthcare inequalities.